MUTU PERMEN JELLI BUAH NAGA MERAH (Hylocereus polyrhizus) DENGAN PENAMBAHAN KARAGENAN DAN GUM ARAB - Jumri '; Yusmarini '; Netti Herawati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to obtain the best quality of the red dragon fruit (Hylocereus polyrhizus) jelly which added of carrageenan and arabic gum. This study is held experimentally by using CRD (Complete Randomized Design) of five treatments and replications. There are five types of jelly are researched, those are KG1 (carrageenan and arabic gum ratio10,5% : 0,5%), KG2 (carrageenan and arabic gum ratio 10,0% : 1,0%), KG3 (carrageenan and arabic gum ratio 9,5% : 1,5%), KG4 (carrageenan and arabic gum ratio 9,0% : 2,0%) and KG5 (carrageenan and arabic gum ratio  8,5% : 2,5%). Data were analized by ANOVA and DNMRT at the level of 5%. The result showed that there is no significant influence (P>0,05) of ratio carrageenan and arabic gum in water, ash, sugar reduction, color, and flavor but significant is influence (P>0,05) in pH, texture, taste, and overall assessment. The best jelly KG1 with a water 30,48%, ash 2,5%, pH 5,3, sugar reduction 22,70%. Organoleptic scores of KG1 are 1,29 (color), 1,74 (taste), 2,95 (flavour), 2,52 (texture) and comprehersive score (1,98).   Keywords: jelly, dragon fruit, carrageenan, arabic gum